Evidence for a specific and critical role of mitogen‐activated protein kinase 20 in uni‐to‐binucleate transition of microgametogenesis in tomato. Issue 1 (18th April 2018) - Chen, Lifei; Yang, Dandan; Zhang, Youwei; Wu, Limin; Zhang, Yaoyao; Ye, Lei; Pan, Changtian; He, Yanjun; Huang, Li; Ruan, Yong‐Ling; Lu, Gang
Summary: Mitogen‐activated protein kinases (MAPKs) regulate diverse aspects of plant growth. However, their potential role in reproductive development remains elusive. Here, we discovered an unique role of SlMPK20, a plant‐specific group D MAPK, in pollen development in tomato. RNAi‐mediated suppression of SlMPK20 or its knockout using CRISPR/Cas9 significantly reduced or completely abolished pollen viability, respectively, with no effects on maternal fertility. Cell biology and gene expression analyses established that SlMPK20 exerts its role specifically at the uni‐to‐binucleate transition during microgametogenesis. This assertion is based on the findings that the transgenic pollen was largely arrested at the binucleate stage with the appearance of subcellular abnormality at the middle uninucleate microspore stage; and SlMPK20 mRNA and SlMPK20‐ GUS signals were localized in the tetrads, uninuclear microspores and binuclear pollen grains but not in microspore mother cells or mature pollen grains. Transcriptomic and proteomic analyses revealed that knockout of SlMPK20 significantly reduced the expression of a large number of genes controlling sugar and auxin metabolism and signaling in anthers. Finally, protein–protein interaction assays identified SlMYB32 as a putative target protein of SlMPK20. We conclude that SlMPK20 specifically regulates post‐meiotic pollen development through modulating sugar and auxin metabolism and signaling.